Re-Evaluating the Internal Phylogenetic Relationships of Collembola by Means of Mitogenome Data - Cucini, Claudio; Fanciulli, Pietro P.; Frati, Francesco; Convey, Peter; Nardi, Francesco; Carapelli, Antonio (Genes, 2021)
Collembola are an ancient and early diverging lineage of basal hexapods that occur in virtually all terrestrial habitats on Earth. Phylogenetic relationships between the different orders of Collembola are fiercely debated. Despite a range of studies and the application of both morphological and genetic approaches (singly or in combination) to assess the evolutionary relationships of major lineages in the group, no consensus has been reached. Several mitogenome sequences have been published for key taxa of the class (and their number is increasing rapidly). Here, we describe two new Antarctic Collembola mitogenomes and compare all complete or semi-complete springtail mitogenome sequences available on GenBank in terms of both gene order and DNA sequence analyses in a genome evolution and molecular phylogenetic framework. With minor exceptions, we confirm the monophyly of Poduromorpha and Symphypleona sensu stricto (the latter placed at the most basal position in the springtail phylogenetic tree), whereas monophyly of Neelipleona and Entomobryomorpha is only supported when a handful of critical taxa in these two lineages are excluded. Finally, we review gene order models observed in the class, as well as the overall mitochondrial nucleotide composition.